Increasing protein distribution has no effect on changes in lean mass during a rugby preseason - MacKenzie-Shalders, K. L.; King, N. A.; Byrne, N. M.; Slater, G. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Increasing the frequency of protein consumption is recommended to stimulate muscle hypertrophy with resistance exercise. This study manipulated dietary protein distribution to assess the effect on gains in lean mass during a rugby preseason. Twenty-four developing elite rugby athletes (age 20.1 ± 1.4 years, mass 101.6 ± 12.0 kg; M ± SD) were instructed to consume high biological value (HBV) protein at their main meals and immediately after resistance exercise while limiting protein intake between meals. To manipulate protein intake frequency, the athletes consumed 3 HBV liquid protein supplements (22 g protein) either with main meals (bolus condition) or between meals (frequent condition) for 6 weeks in a 2 × 2 crossover design. Dietary intake and change in lean mass values were compared between conditions by analysis of covariance and correlational analysis. The dietary manipulation successfully altered the protein distribution score (average number of eating occasions containing > 20 g of protein) to 4.0 ± 0.8 and 5.9 ± 0.7 (p < .01) for the bolus and frequent conditions, respectively. There was no difference in gains in lean mass between the bolus (1.4 ± 1.5 kg) and frequent (1.5 ± 1.4 kg) conditions (p = .91). There was no clear effect of increasing protein distribution from approximately 4-6 eating occasions on changes in lean mass during a rugby preseason. However, other dietary factors may have augmented adaptation.